Return-to-Play after Lower Limb Muscle Injury in Football The Italian Consensus Conference Guidelines - Bisciotti, Gian Nicola; Corsini, Alessandro; Volpi, Piero; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Return to training (RTT) and return to play (RTP) decisions making process in football are currently based on expert's opinion. However, there are no consensus guidelines on evidence-based decision-making. This book provides a framework for evidence-based decision-making both in RTT and RTP following lower-limb muscle injuries sustained in football. Based on the (3z(BItalian Consensus Conference (2019) on return-to-play after lower limb muscle injury in football(3y(B, it provides a list of RTT and RTP criteria after such injuries compiled by orthopedic surgeons, sports physicians, radiologists, rehabilitation physicians, sport physiologists, general surgeons, family physicians, physiotherapists, physical trainers and psychologists working in elite football in Italy. The book identifies the main criteria for RTT and RTP following injuries involving the most important muscle groups, i.e. quadriceps, hamstring, hip adductor, hip external rotator, iliopsoas and soleus-gastrocnemius. As such it is a valuable reference resource for practitioners making RTT and RTP decisions making process.s
1 The return to training general(RTT) principles -- 2 The return to play (RTP) general principles -- 3 RTT and RTP after quadriceps injury -- 4 RTT and RTP after hamstring injury -- 5 RTT and RTP after adductors injuries -- 6 RTT and RTP after external hip rotators injury -- 7 RTT and RTP after soleus-gastrocnemius muscle injuries.
Keywords: Sports medicine; Sports sciences; Medical sciences; Physical therapy; Biomechanics; Radiology; Sports Medicine; Sport Science; Health Sciences; Physiotherapy; Biomechanics; Radiology; Lower Extremity -- injuries; Muscles -- injuries; Athletic Injuries -- therapy; Soccer; Return to Sport; Guidelines as Topic